Answer :

PunIntended

Answer and Explanation:

When you raise a power to a power, you multiply the two exponents. As you can see, [tex](a^{m})^{n} = a^{mn}[/tex] .

1. [tex](k^{4})^{5} = k^{4*5} = k^{20}[/tex] . So, the answer is k^20

2. [tex](8^{2})^{7} = 8^{2*7} = 8^{14}[/tex] . So, the answer is 8^14

3. When you have two items that you're taking the power of, you put the exponent on both terms. For example, here:

[tex](4p^{4})^{3} = 4^{3} * p^{4*3} = 4^3 * p^{12} = 64p^{12}[/tex] . So, the answer is 64p^12

Other Questions